Pengaruh Corporate Social Responsibility dan Good Corporate Governance Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Yang Terdaftar di BEI Tahun 2016-2018) - Elen Manura Wijaya; Sri Wibawani; Firda Ayu Amalia (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2022)
This study aims to determine the effect of Corporate Social Responsibility and Good Corporate Governance on corporate value. The research method used is the Structural Equation Modeling method. The sample of this research is companies listed on the Indonesia Stock Exchange in 2016-2018 using purposive sampling. 24 companies meet the criteria as a research sample. The results of this study indicate that CSR and GCG have a significant negative effect on firm value.